Volume-Based Feeding in the Critically Ill Patient. (August 2015) - McClave, Stephen A.; Saad, Mohamed A.; Esterle, Mark; Anderson, Mary; Jotautas, Alice E.; Franklin, Glen A.; Heyland, Daren K.; Hurt, Ryan T.
Introduction: Critically ill patients placed on enteral nutrition (EN) are usually underfed. A volume-based feeding (VBF) protocol designed to adjust the infusion rate to make up for interruptions in delivery should provide a greater volume of EN than the more common fixed hourly rate-based feeding (RBF) method. Methods: This single-center, randomized (3:1; VBF/RBF) prospective study evaluated critically ill patients on mechanical ventilation expected to receive EN for ≥3 days. Once goal rate was achieved, the randomized feeding strategy was implemented. In the VBF group, physicians used a total goal volume of feeds to determine an hourly rate. For the RBF group, physicians determined a constant hourly rate of infusion to meet goal feeds. Results: Sixty-three patients were enrolled in the study with a mean age of 52.6 years (60% male). Six patients were excluded after randomization because of early extubation. The VBF group (n = 37) received 92.9% of goal caloric requirements with a mean caloric deficit of −776.0 kcal compared with the RBF group (n = 20), which received 80.9% of goal calories ( P = .01) and a caloric deficit of −1933.8 kcal ( P = .01). Uninterrupted EN was delivered for 51.7% of all EN days in VFB patients compared with 54.5% in RBF patients. On days when feeding was interrupted, VFB patients overall received a mean 77.6% of goal calories (while RBF patients received 61.5% of goal calories, P = .001). No vomiting, regurgitation, or feeding intolerance occurred due to VBF. Conclusions: A VBF strategy is safe and improves delivery to better meet caloric requirements than the standard more commonly used rate-based strategy.